Pengaruh Pembiayaan Pemerintah di Sektor Pendidikan dan Kesehatan Terhadap Indeks Kualitas Manusia Serta Pertumbuhan Ekonomi pada Kabupaten/Kota Provinsi Bali Tahun 2011-2015 - Angga Dianaputra, I Gede Komang; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
This research was to analyze the influence of government financing in the education and health sectors against the index of the quality of human as well as economic growth. This research was conducted in the whole district/municipality in the province of Bali. The data used in this research is secondary data, whereas the methods of analysis used i.e. path analysis. Based on the results of the analysis it was found that government financing in the education and health sector a positive and significant effect against the human quality indices. Government financing in the education and health sector have a significant and positive influence toward economic growth. Human quality indices have a significant and positive influence toward economic growth. Government financing in the education and health sectors have influence indirectly against economic growth through the index of the quality of human beings. The indirect influence is indicated by the variable index of human qualities is intervening as variables.
Keywords: Pembiayaan Pemerintah di Sektor Pendidikan, Pembiayaan Pemerintah di Sektor Kesehatan, Indeks Kualitas Manusia, Pertumbuhan Ekonomi